Factors of development of dependence on virtual environment - Shershniova, Tatiana V.; Drozdov, Igor I. (Journal of the Belarusian State University. Ecology, 2018)
This article reviews the problem of dependence on virtual reality. The last two decades are due to a fairly rapid growth in the development of virtual technologies, which made a new type of dependence – dependence on virtual reality. The main factors of virtual addiction emergence were shown and analyzed. Also, the main socio-psychological signs that can be represented as factors of the occurrence of addictive behavior were analyzed and disclosed. Finally,we have made a comparison between the dependence on virtual reality and the dependence on psychoactive substances.